Impact of product design and sales promotion on eiger customer loyalty - Adisti, Yuniar Rahma; Lusianti, Dina; Faidah, Faridhatun (SHM Publisher, 2024)
The needs of society and developing lifestyles will result in hobbies also developing, such as the hobby of adventuring in the wild. One brand of outdoor equipment is Eiger. This research analyzes the influence of Product Design and sales Promotion on Customer Loyalty through Consumer Satisfaction. The object of this research is the Eiger product in Kudus. The data used in this research was by distributing questionnaires via online form. The instrument test in this study used a reliability test and validity test. The analytical tool in this research uses SEM-AMOS. This research shows that product design has no effect on consumer satisfaction. Sales promotions have a positive and significant effect on consumer satisfaction. Product design has a positive and significant effect on customer loyalty. Sales promotions do not affect customer loyalty. Consumer satisfaction does not affect customer loyalty. Product design and sales promotions on customer loyalty through consumer satisfaction have a weak mediating influence. Product design, sales promotions, and consumer satisfaction are important in shaping consumer perceptions of loyalty. This perception will influence customer attitudes and behavior. Therefore, companies must design good strategies so that consumers can behave and behave as expected.